Approaches to the World: The Multiple Dimensions of the Social - Lindemann, Gesa (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Responding to the critique of methodological ethnocentrism, Lindemann develops a new general social theory that is also highly sensitive to socio-cultural differences. Drawing on Helmuth Plessner’s theory of excentric positionality, social order is understood as a symbolically and technically mediated spatio-temporal order that is integrated by an order of violence. Lindemann hereby brings together three significant aspects of recent debates: the debates on the necessity of a theoretical turn (such as the linguistic turn, the material turn, the body turn, the pictorial turn and the spatial turn); second, the debates on the actor status of non-humans and the borders of the social world, and third, the discussions about the role of violence in structuring social processes.